The Competency of Science Teachers in Implementation of Online Learning In Covid-19 Pandemic Period at SMPN 2 Kramatwatu Serang - Khadijah, Ijah (CV. Creative Tugu Pena, 2021)
The purpose of this study was to describe the competence of science teachers at the junior high school level in implementing online learning during the Covid-19 pandemic. Explain how the steps that science teachers must take in overcoming the challenges of exact learning (IPA), as well as how to deal with the psychological dynamics of students who experience difficulties in the science learning process. The method used is a qualitative approach. Data collection techniques used were interviews, observation, documentation study, and audio-visual information. The data analysis used is to draw conclusions to produce descriptive meanings as the final result of the research process. The conclusion of this study is that the competence of science teachers in implementing learning during the Covid 19 pandemic at SMPN 2 Kramatwatu, Serang consists of 1) teacher skills in operating internet-based technology devices into online learning; 2) teacher skills in managing or managing situations faced when online learning is implemented; 3) teacher skills in understanding the psychological conditions and mental health of students; 4) teacher skills in making innovations and creativity in science learning. Keywords: Competence, Science Teacher, Online Learning, Covid-19